Master batch, preparation method thereof, light diffusion plate and refrigerator
By combining nitrogen-doped graphene with nanotitanium dioxide, a wide spectrum visual light response photocatalyst masterbatch was prepared, which solved the problem that the existing antibacterial coating could not meet the requirements of visual photocatalytic and food contact, achieved efficient antibacterial and odor reduction effects, and simplified the manufacturing process.
Patent Information
- Application Number
- CN202311316264.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
The existing antibacterial coatings cannot meet the high visual photocatalytic effect and meet the requirements of food contact at the same time, and there are problems with complex manufacturing processes caused by the spraying process.
By combining nitrogen-doped graphene with nanotitanium dioxide, a graphene-titanium dioxide composite photocatalyst composite powder with wide spectrum and visual light response characteristics was prepared, and the masterbatch was added to plastic particles, and the spraying process was omitted.
It achieves antibacterial properties with excellent catalytic effects under visible light conditions, and simplifies the manufacturing process, which is suitable for carrying at the light source on the refrigerator surface.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refrigerator materials, and in particular relates to a masterbatch, a preparation method thereof, a light diffusion plate and a refrigerator. Background Art
[0002] When the refrigerator is in use, mixing ingredients will produce cross-flavors. Pathogens carried by fresh fish, seafood, fruits and vegetables will cause bacteria to grow inside the refrigerator and cause peculiar smell in the air, increasing health risks. High-end refrigerator air duct covers usually choose to use surface light sources as decorations, which have a large surface area. If the light diffuser can be injection molded with photocatalyst PP masterbatch, and it is a wide spectrum with visible light response, it will greatly improve the antibacterial and odor-removing effect inside the refrigerator and bring users a better user experience. However, traditional photocatalysts have problems such as narrow light response range (mainly ultraviolet light), poor visible light catalytic effect, non-permanence, and toxic substances, and cannot meet the purpose of use. At present, the common method is to improve the antibacterial and odor-removing effect inside the refrigerator by adding antibacterial coatings, which is usually achieved by adding Ag particle antibacterial agents or graphene; photocatalysts are usually added with TiO2. However, ordinary photocatalyst-grade TiO2 does not have a visible light response effect, or the catalytic effect is poor, and it cannot achieve the antibacterial and odor-removing effect, so it is not suitable for installation at the surface light source.
[0003] Chinese patent CN111910443A discloses a graphene antibacterial coating and its preparation method. The antibacterial mechanism of the coating is physical antibacterial of graphene and it does not have photocatalytic properties. Chinese patent CN113430620B discloses a metal-based graphene oxide antibacterial coating, its preparation method and its application, and specifically discloses a method for preparing a metal-based graphene oxide antibacterial coating based on magnetic field-assisted scanning jet electrodeposition, which is mainly based on metal plating and is suitable for the surface of metal substrates. Chinese patent CN116535911A discloses a visible light photocatalyst coating and its preparation method, and the photocatalyst additive uses bismuth nanomaterials.
[0004] In summary, although a lot of research has been done on antibacterial coatings in the prior art, none of the above coatings can simultaneously meet the requirements of high visible light catalytic effect and food contact, and there is a problem of complex manufacturing process caused by the spraying process. Summary of the invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is that the existing antibacterial coating cannot simultaneously meet the requirements of high visible light catalytic effect and food contact, and there is a problem of complex manufacturing process due to the spraying process. A masterbatch with the characteristics of wide spectrum, visible light response, high catalytic activity, good antibacterial performance and omitting the spraying process, a preparation method thereof, a light diffuser plate and a refrigerator are proposed.
[0006] In order to solve the technical problem, the technical solution adopted by the present invention is:
[0007] On one hand, the present invention provides a method for preparing a masterbatch, comprising a step of preparing nitrogen-doped graphene, a step of preparing a graphene-titanium dioxide composite photocatalyst composite powder, and a step of preparing a photocatalyst masterbatch; the step of preparing nitrogen-doped graphene comprises:
[0008] A graphene oxide dispersion liquid with a mass fraction of 1 to 3% is prepared; ammonia water is used as a nitrogen source, and the graphene oxide dispersion liquid and the ammonia water are mixed in a ratio of 1 to 2:1 in volume fraction; after heating in a closed container for reaction, the mixed liquid is taken out and cooled to room temperature, and freeze-dried to obtain a powder; a tube furnace is heated to 450 to 500° C., the powder is put into the tube furnace from one side, and the powder is pushed out from the other side to obtain nitrogen-doped graphene.
[0009] Preferably, the nitrogen-doped graphene preparation step further comprises:
[0010] Select graphene oxide, set the speed of the homogenizer to 4000-6000 r / min, use one of sodium dodecylbenzenesulfonate and sodium p-toluenesulfonate as a dispersant, slowly add the graphene oxide into distilled water to prepare a graphene oxide dispersion with a mass fraction of 1-3%, wherein the dispersion is uniform and in an emulsion state;
[0011] Using ammonia water as a nitrogen source, the graphene oxide dispersion and the ammonia water are mixed in a ratio of 1 to 2:1 in volume fraction, the temperature is raised to 180° C. in a sealed container, and after maintaining for 45 to 60 minutes, the mixed solution is taken out and cooled to room temperature, and the mixed solution is poured into a freeze dryer tray for freeze drying, and the freeze-dried powder is taken out after 24 hours;
[0012] The tube furnace is heated to 450-500° C., the powder is put into the tube furnace from one side, and the powder is pushed out from the other side at a speed of 0.5 m / s to obtain nitrogen-doped graphene.
[0013] Preferably, the steps for preparing the graphene-titanium dioxide composite photocatalyst composite powder include:
[0014] Adding nitrogen-doped graphene to an aqueous solution containing 10% NMP to prepare a nitrogen-doped graphene NMP dispersion with a concentration of 1 to 5%;
[0015] Dissolving nano-photocatalyst titanium dioxide in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10 to 35%, mixing the nano-photocatalyst titanium dioxide aqueous solution and nitrogen-doped graphene NMP dispersion in a weight ratio of 1 to 5:1, dispersing in an ultrasonic disperser to obtain a dispersed mixed solution;
[0016] The dispersed mixed liquid is placed in a high-pressure homogenizer for homogenization, and then freeze-dried to obtain a graphene-titanium dioxide composite photocatalyst composite powder.
[0017] Preferably, the step of preparing the graphene-titanium dioxide composite photocatalyst composite powder further comprises:
[0018] Under the condition of a homogenizer with a rotation speed of 4000-5000 r / min, adding nitrogen-doped graphene to a 10% NMP aqueous solution to prepare a 1-5% nitrogen-doped graphene NMP dispersion;
[0019] Dissolve nano-photocatalyst titanium dioxide with a particle size of 1 to 5 nm in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10 to 35%, mix the nano-photocatalyst titanium dioxide aqueous solution and nitrogen-doped graphene NMP dispersion at a weight ratio of 1 to 5:1, place in an ultrasonic disperser and disperse for 5 to 10 minutes to obtain a dispersed mixed solution;
[0020] The dispersed mixed liquid is placed in a high-pressure homogenizer, homogenized at a pressure of 20 to 30 MPa, and freeze-dried at -30 to -40°C for 36 hours to obtain the graphene-titanium dioxide composite photocatalyst composite powder.
[0021] Preferably, the photocatalyst masterbatch preparation step comprises:
[0022] Put PP and silane coupling agent into a mixer, stir and mix, so that the silane coupling agent is evenly adhered to the PP, to obtain a mixture A;
[0023] Putting the flow modifier, the nucleating agent and the antioxidant into the mixer, and mixing them evenly with the mixture A to obtain a mixed raw material;
[0024] The mixed raw materials are added into a twin-screw extruder through a metering hopper, and the graphene-titanium dioxide composite photocatalyst composite powder is added through a side feeding metering hopper, and the photocatalyst PP masterbatch is obtained through melt blending, extrusion stripping, cooling, air drying, pelletizing and drying.
[0025] Preferably, the photocatalyst masterbatch preparation step further comprises:
[0026] Put the PP and the silane coupling agent into a mixer, the speed of the mixer is any value between 200 and 500 rpm, and stir and mix for 1 to 3 minutes, so that the silane coupling agent is evenly adhered to the PP, to obtain a mixture A;
[0027] Adding a flow modifier, a nucleating agent, and an antioxidant into the mixer, the rotating speed of the mixer is any value between 200 and 500 rpm, stirring and mixing for 3 to 6 minutes, and mixing them evenly with the mixture A to obtain a mixed raw material;
[0028] The mixed raw materials are added into a twin-screw extruder through a metering hopper, and the graphene-titanium dioxide composite photocatalyst composite powder is added through a side feeding metering hopper, the temperature is set to any value between 170 and 230° C., the rotation speed is set to any value between 200 and 500 rpm, and the shear strength is medium. After melt blending, extrusion, cooling, air drying, pelletizing, and drying, a photocatalyst PP masterbatch is obtained.
[0029] Preferably, in parts by mass, the PP is selected from any value between 20 and 60 parts, the graphene-titanium dioxide composite photocatalyst composite powder is selected from any value between 40 and 80 parts, the flow modifier is selected from any value between 1 and 2 parts, the nucleating agent is selected from any value between 0.1 and 0.5 parts, the antioxidant is selected from any value between 0.3 and 1 parts, and the silane coupling agent is selected from any value between 0.4 and 1 parts.
[0030] The present invention also provides a masterbatch prepared by the method for preparing the masterbatch according to any of the above technical solutions, wherein the masterbatch comprises nitrogen-doped graphene, the number of layers of the nitrogen-doped graphene is 2 to 4, and the particle size is 5 to 10 nm.
[0031] Another aspect of the present invention provides a light diffuser plate, which is obtained by injection molding using the above masterbatch.
[0032] The present invention further provides a refrigerator, wherein the light diffusion plate of the surface light source at the back of the refrigerator is obtained by injection molding the masterbatch.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention provides a method for preparing a masterbatch, wherein graphene is modified by nitrogen doping and compounded with nano titanium dioxide to obtain a graphene-titanium dioxide composite photocatalyst composite powder, the high conductivity of graphene is used to improve the catalytic activity of titanium dioxide, and the graphene-titanium dioxide composite photocatalyst composite powder is added to plastic particles to obtain a masterbatch, wherein the masterbatch has the characteristics of a wide spectrum and visible light response, and has an excellent catalytic effect under visible light conditions;
[0035] The present invention also provides a light diffusion plate, which is obtained by injection molding using the masterbatch as a raw material. Under the irradiation of a surface light source, the light diffusion plate undergoes a catalytic reaction to achieve the effects of antibacterial and odor reduction. DETAILED DESCRIPTION
[0036] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.
[0037] On one hand, the present invention provides a method for preparing a masterbatch, comprising a nitrogen-doped graphene preparation step, a graphene-titanium dioxide composite photocatalyst composite powder preparation step, and a photocatalyst masterbatch preparation step; the nitrogen-doped graphene preparation step comprises: preparing a graphene oxide dispersion with a mass fraction of 1-3%; using ammonia water as a nitrogen source, mixing the graphene oxide dispersion with the ammonia water in a ratio of 1-2:1 in volume fraction, heating the mixture in a sealed container for reaction, taking out the mixture, cooling it to room temperature, and freeze-drying it to obtain a powder; heating a tube furnace to 450-500° C., putting the powder in from one side of the tube furnace, and pushing the powder out from the other side to obtain the nitrogen-doped graphene. The preparation method of the masterbatch is to modify the graphene by nitrogen doping, and compound it with nano titanium dioxide to obtain a graphene-titanium dioxide composite photocatalyst composite powder, utilize the high conductivity of graphene to improve the catalytic activity of titanium dioxide, and add the graphene-titanium dioxide composite photocatalyst composite powder into plastic particles to obtain a masterbatch, which has the characteristics of wide spectrum and visible light response. The present invention specifically defines the preparation method of nitrogen-doped graphene, because the nitrogen doping rate of the nitrogen-doped graphene obtained by the nitrogen doping method can reach 8-10%, the nitrogen atom directly replaces C to enter the graphene lattice, and can be connected with hydroxyl or amine. After nitrogen doping, it is reduced by high temperature in a high temperature tube furnace to reduce the hydroxyl and carboxyl groups at the edge of the original graphene to carbon dioxide and water, which can further increase the surface area and conductivity of the graphene. The existing preparation of nitrogen-doped graphene is to first reduce graphene oxide with hydrazine hydrate, and then graft functional groups with hydroxyl groups on the surface of the reduced graphene oxide through a diazo addition reaction, which is not a nitrogen-doping reaction in essence. Furthermore, the graphene oxide of the present invention is selected from graphene oxide prepared by freeze-drying, the nitrogen source is ammonia water, and the graphene oxide is directly doped with nitrogen, so the graphene oxide has higher activity. The present invention further defines the use of nano-photocatalyst titanium dioxide and nitrogen-doped graphene prepared by the above preparation method to compound to obtain a graphene-titanium dioxide composite photocatalyst composite powder, because graphene has extremely high conductivity. In the nitrogen-doped graphene / titanium dioxide system, the nitrogen-doped graphene improves the electron conduction efficiency, so that the photogenerated carriers of titanium dioxide are conducted to the graphene surface, thereby reducing the recombination efficiency of the electron-hole pairs of titanium dioxide and improving the photocatalytic efficiency; high-temperature reduced graphene oxide has a very large specific surface area and a strong adsorption force, adsorbs molecules or bacteria to be degraded on the graphene surface, and reacts with the photogenerated carriers transferred on its surface to form free radicals and active oxygen. Therefore, in the composite system, graphene is used as a carrier of the photocatalytic reaction, which greatly improves the efficiency of the photocatalytic reaction; in addition, the surface of the nitrogen-doped graphene prepared in this scheme cannot form a large π bond, and can form a Ti-OC bond with nano-titanium dioxide, thereby increasing the valence band width of titanium dioxide, reducing the band gap width, and increasing the visible light absorption rate.
[0038] In a preferred embodiment, the nitrogen-doped graphene preparation step further includes: selecting graphene oxide, setting the speed of the homogenizer to 4000-6000 r / min, using one of sodium dodecylbenzenesulfonate and sodium p-toluenesulfonate as a dispersant, slowly adding the graphene oxide to distilled water to obtain a graphene oxide dispersion with a mass fraction of 1-3%, and the dispersion is uniform in an emulsion state; using ammonia water as a nitrogen source, and mixing the graphene oxide dispersion with a volume fraction of ammonia water: graphene oxide dispersion of 1-3%. Mix the graphene oxide dispersion and the ammonia water in a ratio of 2:1, heat to 180°C in a sealed container, keep for 45-60 minutes, take out the mixed solution and cool to room temperature, pour the mixed solution into the freeze dryer tray, freeze dry, and take out the freeze-dried powder after 24 hours; heat the tube furnace to 450-500°C, put the powder in from one side of the tube furnace, and push the powder out from the other side at a speed of 0.5m / s to obtain nitrogen-doped graphene. It can be understood that the speed of the mass emulsifier can also be 4500r / min, 5000r / min, 5500r / min and any point value within the range; the mass fraction of the graphene oxide dispersion can also be 2%, and the tube furnace can also be heated to 460°C, 470°C, 480°C, 490°C and any point value within the range.
[0039] In a preferred embodiment, the preparation steps of the graphene-titanium dioxide composite photocatalyst composite powder include: adding nitrogen-doped graphene to a 10% NMP aqueous solution to obtain a nitrogen-doped graphene NMP dispersion with a concentration of 1-5%; taking nano-photocatalyst titanium dioxide and dissolving it in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10-35%, mixing them in a weight ratio of nano-photocatalyst titanium dioxide aqueous solution: nitrogen-doped graphene NMP dispersion of 1-5:1, placing them in an ultrasonic disperser for dispersion to obtain a dispersed mixed solution; placing the dispersed mixed solution in a high-pressure homogenizer for homogenization, and freeze-drying to obtain a graphene-titanium dioxide composite photocatalyst composite powder. The preparation steps of the graphene-titanium dioxide composite photocatalyst composite powder further include: adding nitrogen-doped graphene to a 10% NMP aqueous solution under the condition of a homogenizer with an emulsifier speed of 4000-5000 r / min to prepare a nitrogen-doped graphene NMP dispersion with a concentration of 1-5%; dissolving nano-photocatalyst titanium dioxide with a particle size of any value between 1 and 5 nm in water to prepare a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10-35%, mixing the nano-photocatalyst titanium dioxide aqueous solution: nitrogen-doped graphene NMP dispersion at a weight ratio of 1-5:1, placing the mixture in an ultrasonic disperser for dispersion for 5-10 minutes to obtain a dispersed mixed solution; placing the dispersed mixed solution in a high-pressure homogenizer, homogenizing it at a pressure of 20-30 MPa, and freeze-drying it at -30--40°C for 36 hours to obtain the graphene-titanium dioxide composite photocatalyst composite powder.
[0040] In a preferred embodiment, the photocatalyst masterbatch preparation step includes: putting PP and a silane coupling agent into a mixer, stirring and mixing, so that the silane coupling agent is evenly adhered to the PP to obtain a mixture A; putting a flow modifier, a nucleating agent, and an antioxidant into the mixer, and mixing them evenly with the mixture A to obtain a mixed raw material; adding the mixed raw material into a twin-screw extruder through a metering hopper, and adding the graphene-titanium dioxide composite photocatalyst composite powder through a side feeding metering hopper, and obtaining a photocatalyst PP masterbatch through melt blending, extrusion drawing, cooling, air drying, pelletizing, and drying. The photocatalyst masterbatch preparation step further includes: putting the PP and the silane coupling agent into a mixer, the speed of the mixer is any value between 200 and 500 rpm, stirring and mixing for 1 to 3 minutes, so that the silane coupling agent is uniformly adhered to the PP to obtain a mixture A; putting a flow modifier, a nucleating agent, and an antioxidant into the mixer, the speed of the mixer is any value between 200 and 500 rpm, stirring and mixing for 3 to 6 minutes, and mixing them evenly with the mixture A to obtain a mixed raw material; adding the mixed raw material into a twin-screw extruder through a metering hopper, and adding the graphene-titanium dioxide composite photocatalyst composite powder through a side feeding metering hopper, setting the temperature to any value between 170 and 230° C., the speed to any value between 200 and 500 rpm, and medium shear strength, and obtaining a photocatalyst PP masterbatch through melt blending, extrusion drawing, cooling, air drying, pelletizing, and drying. Regarding the above steps for preparing the photocatalyst masterbatch, it should be noted that graphene itself is difficult to disperse in PP, but the present invention modifies the graphene by nitrogen doping, and the nitrogen-doped graphene and titanium dioxide are tightly combined together through van der Waals forces. The good dispersibility of titanium dioxide improves the dispersibility of the nitrogen-doped graphene in the PP material.
[0041] In a preferred embodiment, in parts by mass, the PP is selected from any value between 20 and 60 parts, the graphene-titanium dioxide composite photocatalyst composite powder is selected from any value between 40 and 80 parts, the flow modifier is selected from any value between 1 and 2 parts, the nucleating agent is selected from any value between 0.1 and 0.5 parts, the antioxidant is selected from any value between 0.3 and 1 parts, and the silane coupling agent is selected from any value between 0.4 and 1 parts.
[0042] The present invention also provides a masterbatch prepared by the method for preparing a masterbatch according to any of the above technical solutions, wherein the masterbatch includes nitrogen-doped graphene, wherein the number of layers of the nitrogen-doped graphene is 2 to 4 and the particle size is 5 to 10 nm. The antibacterial mechanism of the masterbatch includes: 1. The nitrogen-doped graphene after high-temperature reduction has a higher specific surface area, can adsorb more organic matter, and the "defects" on the surface caused by high temperature have raised graphene sheet structures, which are shaped like blades and have a cutting effect on bacterial cell membranes; 2. Nano-titanium dioxide photocatalytic effect; 3. The synergistic effect of nitrogen-doped graphene and titanium dioxide, graphene enhances the absorption rate of nano-titanium dioxide to visible light and improves the photocatalytic efficiency.
[0043] Another aspect of the present invention provides a light diffuser plate, which is obtained by injection molding using the above masterbatch. The light diffuser plate is obtained by injection molding using the above masterbatch as a raw material (specifically, the PP masterbatch is added to a mixing pot, dried at 100-150°C for 2-6 hours, and then added to an injection molding machine for injection molding). Under the irradiation of a surface light source, the light diffuser plate undergoes a catalytic reaction to achieve the effects of antibacterial and odor reduction.
[0044] The present invention further provides a refrigerator, wherein the light diffusion plate of the surface light source at the back of the refrigerator is obtained by injection molding the masterbatch.
[0045] In order to more clearly and in detail introduce the masterbatch, the preparation method thereof, the light diffuser plate and the refrigerator provided by the embodiments of the present invention, they will be described below in conjunction with specific embodiments.
[0046] Example 1
[0047] 1. Formula composition
[0048] In parts by mass, it includes 54 parts of water-based hydroxy acrylic resin, 41 parts of graphene-titanium dioxide composite photocatalyst, 2 parts of flow modifier, 0.5 parts of nucleating agent, 1 part of antioxidant and 1 part of silane coupling agent.
[0049] 2. Preparation process of PP masterbatch
[0050] According to the above mass ratio, PP and silane coupling agent are put into a high-speed mixer, the speed is 300 rpm, and the stirring and mixing are carried out for 2 minutes, so that the silane coupling agent is uniformly adhered to the PP particles to obtain a mixture A; the flow modifier, the nucleating agent, and the antioxidant are put into the high-speed mixer, mixed with the mixture A, the speed is 300 rpm, and the stirring and mixing are carried out for 5 minutes to make them uniformly mixed; the mixed raw materials are added into the twin-screw extruder through a metering hopper, and the graphene-titanium dioxide composite photocatalyst is added through a side feeding metering hopper, the temperature is set to 200°C, the speed is 300 rpm, and the shear strength is medium. After melt blending, extrusion drawing, cooling, air drying, pelletizing, and drying, PP masterbatch is obtained.
[0051] 3. The preparation process of the above-mentioned graphene-titanium dioxide composite photocatalyst composite powder includes:
[0052] Select graphene oxide, set the speed of the homogenizer to 4000-6000 r / min, use one of sodium dodecylbenzenesulfonate and sodium p-toluenesulfonate as a dispersant, slowly add graphene oxide into distilled water to prepare a graphene oxide dispersion with a mass fraction of 1-3%, and the dispersion is uniform and in an emulsion state;
[0053] Using ammonia water as a nitrogen source, the graphene oxide dispersion and ammonia water are mixed in a ratio of 1 to 2:1 in volume fraction, the temperature is raised to 180° C. in a sealed container, and after maintaining for 45 to 60 minutes, the mixed solution is taken out and cooled to room temperature, and the mixed solution is poured into a freeze dryer tray for freeze drying, and the freeze-dried powder is taken out after 24 hours;
[0054] The tube furnace is heated to 450-500°C, the powder is placed in from one side of the tube furnace, and the powder is pushed out from the other side at a speed of 0.5 m / s to obtain nitrogen-doped graphene;
[0055] Under the condition of a homogenizer with a rotation speed of 4000-5000 r / min, adding nitrogen-doped graphene to a 10% NMP aqueous solution to prepare a nitrogen-doped graphene NMP dispersion with a concentration of 1-5%;
[0056] Dissolve nano-photocatalyst titanium dioxide with a particle size of 1 to 5 nm in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10 to 35%, mix the nano-photocatalyst titanium dioxide aqueous solution and nitrogen-doped graphene NMP dispersion at a weight ratio of 1 to 5:1, place in an ultrasonic disperser and disperse for 5 to 10 minutes to obtain a dispersed mixed solution;
[0057] The dispersed mixed liquid is placed in a high-pressure homogenizer, homogenized at a pressure of 20 to 30 MPa, and freeze-dried at -30 to -40°C for 36 hours to obtain the graphene-titanium dioxide composite photocatalyst composite powder.
[0058] Example 2
[0059] 1. Formula composition
[0060] In parts by mass, the composition comprises 50 parts of water-based hydroxy acrylic resin, 45 parts of graphene-titanium dioxide composite photocatalyst, 2 parts of flow modifier, 0.5 parts of nucleating agent, 1 part of antioxidant and 1 part of silane coupling agent.
[0061] 2. Preparation process of PP masterbatch
[0062] According to the above mass ratio, PP and silane coupling agent are put into a high-speed mixer, the speed is 300 rpm, and the stirring and mixing are carried out for 2 minutes, so that the silane coupling agent is uniformly adhered to the PP particles to obtain a mixture A; the flow modifier, the nucleating agent, and the antioxidant are put into the high-speed mixer, mixed with the mixture A, the speed is 300 rpm, and the stirring and mixing are carried out for 5 minutes to make them uniformly mixed; the mixed raw materials are added into the twin-screw extruder through a metering hopper, and the graphene-titanium dioxide composite photocatalyst is added through a side feeding metering hopper, the temperature is set to 200°C, the speed is 300 rpm, and the shear strength is medium. After melt blending, extrusion drawing, cooling, air drying, pelletizing, and drying, PP masterbatch is obtained.
[0063] 3. The preparation process of the above-mentioned graphene-titanium dioxide composite photocatalyst composite powder includes:
[0064] Select graphene oxide, set the speed of the homogenizer to 4000-6000 r / min, use one of sodium dodecylbenzenesulfonate and sodium p-toluenesulfonate as a dispersant, slowly add graphene oxide into distilled water to prepare a graphene oxide dispersion with a mass fraction of 1-3%, and the dispersion is uniform and in an emulsion state;
[0065] Using ammonia water as a nitrogen source, the graphene oxide dispersion and ammonia water are mixed in a ratio of 1 to 2:1 in volume fraction, the temperature is raised to 180° C. in a sealed container, and after maintaining for 45 to 60 minutes, the mixed solution is taken out and cooled to room temperature, and the mixed solution is poured into a freeze dryer tray for freeze drying, and the freeze-dried powder is taken out after 24 hours;
[0066] The tube furnace is heated to 450-500°C, the powder is placed in from one side of the tube furnace, and the powder is pushed out from the other side at a speed of 0.5 m / s to obtain nitrogen-doped graphene;
[0067] Under the condition of a homogenizing emulsifier rotating speed of 4000-5000 r / min, adding nitrogen-doped graphene into a 10% NMP aqueous solution to prepare a nitrogen-doped graphene NMP dispersion with a concentration of 1-5%;
[0068] Dissolve nano-photocatalyst titanium dioxide with a particle size of 1 to 5 nm in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10 to 35%, mix the nano-photocatalyst titanium dioxide aqueous solution and nitrogen-doped graphene NMP dispersion at a weight ratio of 1 to 5:1, place in an ultrasonic disperser and disperse for 5 to 10 minutes to obtain a dispersed mixed solution;
[0069] The dispersed mixed liquid is placed in a high-pressure homogenizer, homogenized at a pressure of 20 to 30 MPa, and freeze-dried at -30 to -40°C for 36 hours to obtain the graphene-titanium dioxide composite photocatalyst composite powder.
[0070] Comparative Example 1
[0071] 1. Formula composition
[0072] In parts by mass, it includes 54.5 parts of PP resin, 1 part of graphene powder, 40 parts of nano titanium dioxide, 2 parts of flow modifier, 0.5 parts of nucleating agent, 1 part of antioxidant and 1 part of coupling agent.
[0073] 2. Preparation process of PP masterbatch
[0074] According to the above mass ratio, PP and silane coupling agent are put into a high-speed mixer, the speed is 300 rpm, and the stirring and mixing are carried out for 2 minutes, so that the silane coupling agent is uniformly adhered to the PP particles to obtain a mixture A; the flow modifier, the nucleating agent, and the antioxidant are put into the high-speed mixer, mixed with the mixture A, the speed is 300 rpm, and the stirring and mixing are carried out for 5 minutes to make them uniformly mixed; the mixed raw materials are added into the twin-screw extruder through the metering hopper, and the graphene powder and titanium dioxide powder are added through the side feeding metering hopper. The temperature is set to 200°C, the speed is 300 rpm, and the shear strength is medium. After melt blending, extrusion drawing, cooling, air drying, pelletizing, and drying, the PP masterbatch is obtained.
[0075] Performance Testing
[0076] The coatings prepared in Examples 1 and 2 and Comparative Example 1 were tested for their performance, and the results are shown in Table 1.
[0077] Table 1 Performance test results
[0078] Test items Comparison 1 Example 1 Example 2 Antibacterial test / % 95 99 99.1 Formaldehyde removal rate under natural light / % 83 90 93 Benzene removal rate under natural light / % 85% 90 92 TVOC removal rate under natural light / % 90 95 96 Removal rate under natural light / % 89 92 94
Claims
1. A method for preparing a masterbatch, characterized in that: The method comprises the steps of preparing nitrogen-doped graphene, preparing graphene-titanium dioxide composite photocatalyst composite powder, and preparing photocatalyst masterbatch; the nitrogen-doped graphene preparation step comprises: A graphene oxide dispersion liquid with a mass fraction of 1 to 3% is prepared; ammonia water is used as a nitrogen source, and the graphene oxide dispersion liquid and the ammonia water are mixed in a ratio of 1 to 2:1 in volume fraction; after heating in a closed container for reaction, the mixed liquid is taken out and cooled to room temperature, and freeze-dried to obtain a powder; a tube furnace is heated to 450 to 500° C., the powder is put into the tube furnace from one side, and the powder is pushed out from the other side to obtain nitrogen-doped graphene.
2. The method for preparing a masterbatch according to claim 1, characterized in that: The nitrogen-doped graphene preparation step further comprises: Select graphene oxide, set the speed of the homogenizer to 4000-6000 r / min, use one of sodium dodecylbenzenesulfonate and sodium p-toluenesulfonate as a dispersant, slowly add the graphene oxide into distilled water to prepare a graphene oxide dispersion with a mass fraction of 1-3%, wherein the dispersion is uniform and in an emulsion state; Using ammonia water as a nitrogen source, the graphene oxide dispersion and the ammonia water are mixed in a ratio of 1 to 2:1 in volume fraction, the temperature is raised to 180° C. in a sealed container, and after maintaining for 45 to 60 minutes, the mixed solution is taken out and cooled to room temperature, and the mixed solution is poured into a freeze dryer tray for freeze drying, and the freeze-dried powder is taken out after 24 hours; The tube furnace is heated to 450-500° C., the powder is put into the tube furnace from one side, and the powder is pushed out from the other side at a speed of 0.5 m / s to obtain nitrogen-doped graphene.
3. The method for preparing a masterbatch according to claim 1, characterized in that: The steps of preparing the graphene-titanium dioxide composite photocatalyst composite powder include: Adding nitrogen-doped graphene to an aqueous solution containing 10% NMP to prepare a nitrogen-doped graphene NMP dispersion with a concentration of 1 to 5%; Dissolving nano-photocatalyst titanium dioxide in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10 to 35%, mixing the nano-photocatalyst titanium dioxide aqueous solution and nitrogen-doped graphene NMP dispersion in a weight ratio of 1 to 5:1, dispersing in an ultrasonic disperser to obtain a dispersed mixed solution; The dispersed mixed liquid is placed in a high-pressure homogenizer for homogenization, and then freeze-dried to obtain a graphene-titanium dioxide composite photocatalyst composite powder.
4. The method for preparing a masterbatch according to claim 3, characterized in that: The step of preparing the graphene-titanium dioxide composite photocatalyst composite powder further comprises: Under the condition of a homogenizer with a rotation speed of 4000-5000 r / min, adding nitrogen-doped graphene to a 10% NMP aqueous solution to prepare a 1-5% nitrogen-doped graphene NMP dispersion; Dissolve nano-photocatalyst titanium dioxide with a particle size of 1 to 5 nm in water to obtain a nano-photocatalyst titanium dioxide aqueous solution with a mass fraction of 10 to 35%, mix the nano-photocatalyst titanium dioxide aqueous solution and nitrogen-doped graphene NMP dispersion at a weight ratio of 1 to 5:1, place in an ultrasonic disperser and disperse for 5 to 10 minutes to obtain a dispersed mixed solution; The dispersed mixed liquid is placed in a high-pressure homogenizer, homogenized at a pressure of 20 to 30 MPa, and freeze-dried at -30 to -40°C for 36 hours to obtain the graphene-titanium dioxide composite photocatalyst composite powder.
5. The method for preparing a masterbatch according to claim 1, characterized in that: The photocatalyst masterbatch preparation steps include: Put PP and silane coupling agent into a mixer, stir and mix, so that the silane coupling agent is evenly adhered to the PP, to obtain a mixture A; Putting the flow modifier, the nucleating agent and the antioxidant into the mixer, and mixing them evenly with the mixture A to obtain a mixed raw material; The mixed raw materials are added into a twin-screw extruder through a metering hopper, and the graphene-titanium dioxide composite photocatalyst composite powder is added through a side feeding metering hopper, and the photocatalyst PP masterbatch is obtained through melt blending, extrusion stripping, cooling, air drying, pelletizing and drying.
6. The method for preparing a masterbatch according to claim 5, characterized in that: The photocatalyst masterbatch preparation step further comprises: Put the PP and the silane coupling agent into a mixer, the speed of the mixer is any value between 200 and 500 rpm, and stir and mix for 1 to 3 minutes, so that the silane coupling agent is evenly adhered to the PP, to obtain a mixture A; Adding a flow modifier, a nucleating agent, and an antioxidant into the mixer, the rotating speed of the mixer is any value between 200 and 500 rpm, stirring and mixing for 3 to 6 minutes, and mixing them evenly with the mixture A to obtain a mixed raw material; The mixed raw materials are added into a twin-screw extruder through a metering hopper, and the graphene-titanium dioxide composite photocatalyst composite powder is added through a side feeding metering hopper, the temperature is set to any value between 170 and 230° C., the rotation speed is set to any value between 200 and 500 rpm, and the shear strength is medium. After melt blending, extrusion, cooling, air drying, pelletizing, and drying, a photocatalyst PP masterbatch is obtained.
7. The method for preparing a masterbatch according to claim 5, characterized in that: In parts by mass, the PP is selected from any value between 20 and 60 parts, the graphene-titanium dioxide composite photocatalyst composite powder is selected from any value between 40 and 80 parts, the flow modifier is selected from any value between 1 and 2 parts, the nucleating agent is selected from any value between 0.1 and 0.5 parts, the antioxidant is selected from any value between 0.3 and 1 parts, and the silane coupling agent is selected from any value between 0.4 and 1 parts.
8. The masterbatch prepared by the method for preparing the masterbatch according to any one of claims 1 to 7, characterized in that: The masterbatch comprises nitrogen-doped graphene, the nitrogen-doped graphene has 2 to 4 layers and a particle size of 5 to 10 nm.
9. A light diffuser plate, characterized in that: The light diffuser plate is obtained by injection molding the masterbatch according to claim 8.
10. A refrigerator, characterized in that: The refrigerator back surface light source diffuser plate is obtained by injection molding the masterbatch described in claim 8.
Citation Information
Patent Citations
Graphene antibacterial coating and preparation method thereof
CN111910443A
A metal-based graphene oxide antibacterial coating, its preparation method and its application
CN113430620B
Visible light photocatalyst coating and preparation method thereof
CN116535911A